Gravidity, parity, blood pressure and mortality among women in Bangladesh from the HEALS cohort - Maria Argos; Habibul Ahsan; Yu-Hsuan Shih; Molly Scannell Bryan; Faruque Parvez; Keriann Hunter Uesugi; Mohammed Shahriar; Alauddin Ahmed; Tariqul Islam (BMJ Open)
Objectives Despite a hypothesised connection of reproductive history with hypertension and mortality, the nature of this association is poorly characterised. We evaluated the association of parity and gravidity with blood pressure, hypertension and all-cause mortality.Design Prospective cohort study.Setting Health Effects of Arsenic Longitudinal Study cohort in rural Bangladesh.Participants There were 21 634 Bangladeshi women recruited in 2000–2002, 2006–2008 and 2010–2014 included in the present analysis.Methods Reproductive history was ascertained through an interviewer-administered questionnaire at the baseline visit. Blood pressure was measured by a trained study physician following a standard protocol at the baseline visit. Vital status was ascertained at the biennial follow-up of study participants through June 2017. Linear and logistic regression models estimated the relationship between parity and gravidity with blood pressure and hypertension, respectively. Cox proportional hazards models estimated the relationship with all-cause mortality only among women aged >45 years.Results Diastolic blood pressure was lowest in women with parity one (reference) and elevated in nulliparous women (adjusted % change=3.12; 95% CI 1.93 to 4.33) and women with parity >2 (adjusted % change=1.71; 95% CI 1.12 to 2.31). The associations with nulliparity were stronger for women aged >45 years. Similar association patterns were observed with hypertension. Further, in nulliparous women aged >45 years, 265 deaths (6.6%) were ascertained during the follow-up period (median follow-up time=8 years), and we observed suggestive elevated risks of all-cause mortality (adjusted HR 3.83; 95% CI 0.74 to 19.78). The relationships between reproductive history, blood pressure, hypertension and mortality were similar when modelling reproductive history as gravidity rather than parity.Conclusions For women in rural Bangladesh, nulliparity and nulligravidity appear to be associated with higher blood pressure and subsequent elevated risk of mortality.